Landscape patterning created by the southern harvester termite, Microhodotermes viator: Spatial dispersion of colonies and alteration of soils. (March 2019) - McAuliffe, Joseph R.; Hoffman, M. Timm; McFadden, Leslie D.; Bell, Wesley; Jack, Sam; King, Matthew P.; Nixon, Veronica
Abstract: The southern harvester termite ( Microhodotermes viator ) is often associated with large, regularly spaced earthen mounds called heuweltjies in western South Africa . However, there is considerable debate regarding whether or not the termites play any role in either the creation of these mounds or the enrichment of mound soils with calcium carbonate (CaCO3 ) and plant nutrients. Colonies of M. viator are not always associated with heuweltjies. In some environments, the colonies construct small, cemented conical mounds; in others, colonies do not produce any emergent structure above the surrounding soil surface. Examining the spacing and soil conditions associated with these kinds of colonies provided a means of determining the inherent capacity of M. viator colonies to generate a highly regular spatial patterning of CaCO3 - and nutrient-enriched patches. Those colonies were highly overdispersed and soils in altered zones around colonies were enriched with CaCO3, nitrogen, and phosphorus. These are the same characteristics exhibited by heuweltjies; consequently, we conclude that the sustained influence of colonies of M. viator contributes directly to both the uniform spacing of heuweltjies and the accumulation of CaCO3 and plant nutrients within heuweltjies. Highlights: Origin of regular spacing and nutrient enrichment of heuweltjies is unclear. Colonies of Microhodotermes viator have other physical manifestations. All manifestations of colonies exhibit spatial overdispersion and soil enrichment. Heuweltjies exhibit similar overdispersion and soil modifications. Termites contribute directly to spacing and soil conditions of heuweltjies.